FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK (Studi Kasus WP Orang Pribadi yang Terdaftar di KPP Pratama Semarang Barat) - Anita Anggraeni, 14.05.52.0175; Meita Octaviani, Rachmawati (Students' Journal of Accounting and Banking, 2019)
Tax revenue is one source of state funding, increasing tax revenues will increase the productivity of a country, but it turns out there are still many taxpayers who have not fulfilled their tax obligations. Factors related to taxpayer compliance are awareness of taxpayers, knowledge of taxpayers, tax sanctions and tax socialization. The purpose of this study is to test and analyze the effect of taxpayer knowledge, tax sanctions and tax socialization on taxpayer awareness and tax compliance. The population of this study were all taxpayers registered at KPP Pratama West Semarang, which amounted to 64,586 taxpayers. The sample method used is the Accidental Sampling method. The sample in this study amounted to 100 respondents. Data analysis was performed using multiple linear regression models. The results of this study indicate that knowledge of taxpayers, tax sanctions and tax socialization have a positive and significant effect on awareness of taxpayers and taxpayer compliance.